2010
DOI: 10.1111/j.1463-1318.2009.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence and incontinence after anal fistula surgery

Abstract: The overall recurrence rate is acceptable, but high fistulae continue to be difficult to treat. IO identification is also essential for obtaining good results. It is important to identify the patients with preoperative incontinence as they are at a greater risk of deterioration after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 34 publications
2
56
0
7
Order By: Relevance
“…in fact, other studies have found fistula complexity (type, horseshoe extension, and nonidentified internal opening) to be a statistically significant predictor of recurrence. 35,37 several studies have investigated whether previous surgery for recurrent fistula might be a risk factor for postoperative incontinence but did not demonstrate a relationship. 35,37,38 in our study, preoperative detection of sphincter defects was not related to worsening of continence status after fiPs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…in fact, other studies have found fistula complexity (type, horseshoe extension, and nonidentified internal opening) to be a statistically significant predictor of recurrence. 35,37 several studies have investigated whether previous surgery for recurrent fistula might be a risk factor for postoperative incontinence but did not demonstrate a relationship. 35,37,38 in our study, preoperative detection of sphincter defects was not related to worsening of continence status after fiPs.…”
Section: Discussionmentioning
confidence: 97%
“…this factor has also been investigated in other studies but never found to be significantly predictive. 35,36 the use of seton drainage, necessary in case of an extensive abscess as first-line treatment of acute perianal sepsis, may reflect the greater severity of such fistulas. in fact, other studies have found fistula complexity (type, horseshoe extension, and nonidentified internal opening) to be a statistically significant predictor of recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…One hundred and seven records were excluded for various reasons; therefore, 17 full-text articles were assessed for eligibility. Fourteen reports satisfied the inclusion criteria [19,20,[28][29][30][31][32][33][34][35][36][37][38][39], while three studies were excluded because their results were updated in a more recent article [40][41][42] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…6,7,8 Ancak fistülotomiyle tedavi edilen hastalar postoperatif anal sfinkter fonksiyon bozukluğu gelişme riski altındadır; özellikle kadınlar veya kompleks fistüller, preoperatif inkontinans, tekrarlayan hastalık veya önceki anorektal cerrahi geçiren hastalarda risk artmaktadır. 8,9 Ayrıca, basit fistüller için bile fistülotomi bazı hastalarda işlevsel bozukluğa (anal inkontinans) neden olabileceği ve bunun da hastaların yaşam kalitesini olumsuz etkilediği çalışmalarla ortaya konmuştur. 10,11 Fistülotomi ile "yüksek" bir fistül tedavi ederken artan endişe, fistülün seviyesinin yükselmesiyle birlikte cerrahi tedavi sırasında oluşabilecek anal sfinkter hasarına bağlı kontinansın bozulması riskidir.…”
Section: Introductionunclassified